Effects of electromagnetic field on bone healing around commercially pure titanium surface: Histologic and mechanical study in rabbits - Buzzá, Edmur Pereira; Shibli, Jamil Awad; Barbeiro, Roberto Henrique [UNESP]; Barbosa, José Ricardo de Albergaria (Wolters Kluwer, 2003)
Purpose The purpose of this pilot study was to evaluate the histologic and mechanical healing process in dental implants under the action of pulsed electromagnetic field (PEMF). Materials and Methods Forty-eight commercially pure implant fixtures were implanted in tibiae metaphysis of 12 New Zealand white rabbits divided into experimental (PEMF) and control groups. A PEMF with pulse width of 85 Μs and a pulse frequency of 20 Mc was applied for 30 minutes per day. The animals were killed 21 and 42 days after implantation. The mechanical tests were performed in all animals and bone biopsies were prepared for decalcified sections analysis. Results Mechanical tests did not show significant differences between the groups (P > 0.05); however, statistically significant differences were observed over time (P < 0.0001). Similar histologic features were achieved for both groups. Conclusions These results suggest that PEMF stimulation does not improve the bone-healing process around commercially pure dental implants. © 2003 Lippincott Williams & Wilkins, Inc.
Keywords: Dental implants; Electrical stimulation; Mechanical tests; Osseointegration